2021
DOI: 10.1520/jte20190119
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Solar Distiller Productivity by a Black Metallic Plate of Zinc as a Thermal Storage Material

Abstract: The lack of drinking water is a real global problem. Transforming polluted water into freshwater is another problem. Solar distillation seems a simple and economical solution to this problem, but the yield of a solar still is low, and this poses another problem. One of the best ways to improve the productivity of freshwater from solar energy is to incorporate sensible heat energy storage materials; i.e., the temperature elevation of a material allows for the storage of energy, and that is exactly the purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In addition, Khechekhouche et al (Khechekhouche et al 2021) studied the effect of using zinc plate (black metallic) to enhance the e ciency of the solar distiller. It was found that the daily production was 3.894 L/m².day when using the zinc plate versus 2.52 L/m².day for the distiller without the zinc plate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Khechekhouche et al (Khechekhouche et al 2021) studied the effect of using zinc plate (black metallic) to enhance the e ciency of the solar distiller. It was found that the daily production was 3.894 L/m².day when using the zinc plate versus 2.52 L/m².day for the distiller without the zinc plate.…”
Section: Introductionmentioning
confidence: 99%
“…A group of researchers employed aluminum balls fabricated from commercial aluminum sheets in the solar still's basin. Others have used dune sand as an enhancing material; however, the results show that when compared to a solar still without sand, pure water yield is reduced by 1.45 times [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…This method is not attractive due to its low production and performance 3,4 . Many researchers are searching for inexpensive energy‐saving energy storage materials to improve the CSS's thermal performance and production 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…3,4 Many researchers are searching for inexpensive energy-saving energy storage materials to improve the CSS's thermal performance and production. 5,6 Samuel et al 7 added various storage materials (salt balls and sponges) and studied solar still performance. The researchers concluded that the daily production reached 3700 ml/m 2 when using salt in balls, 2.7 L/m 2 for still with the sponge and 2.2 L/m 2 for solar distillation without storage.…”
mentioning
confidence: 99%